Measuring the benefits of tracking medical treatment through RFId. Issue 2 (9th February 2015) - Gastaldi, Luca; Mangiaracina, Riccardo; Miragliotta, Giovanni; Perego, Alessandro; Tumino, Angela
Abstract : Purpose: – Radio frequency identification (RFId) technology has a great potential to improve process efficiency and effectiveness. However, because of the variety of application areas and achievable benefits, structured assessment models are needed to support managers in the adoption decision. The purpose of this paper is to describe a structured method to support the evaluation of the benefits enabled by RFId technology in medical treatment support in the healthcare industry. The method, and its application to an Italian case study, are deeply illustrated so as to increase the knowledge available to decision makers. Design/methodology/approach: – The research underlying this paper has modelled the relationship between the technology and the performance driver of the target process, and then between the performance driver and the measurable key performance indicators of that process. This knowledge, focused on the healthcare industry but still quite general, has been formalised into 12 causal maps. Starting from these maps, a six-step procedure to prioritise the analysis, tailor the maps and adapt (or develop) analytical models to estimate the benefits is presented. The overall method and its application to an Italian case study are deeply illustrated so as to increase the open available knowledge to decision makers. Findings: – The findings are twofold: first, the knowledge represented by the causal maps; and second, the findings of the case study, which shows that efficiency benefits can cover the operative expenses of RFId adoption, but need to be integrated with effectiveness benefits in order to fully justify the investment costs. Originality/value: – The paper provides a contribution for both researchers and practitioners. As the former are concerned, the paper is a first attempt to fill the existing lack of structured approaches concerning the evaluation of potential benefits of RFId for product traceability within a healthcare facility. As for the latter, the presented method has been developed to practically support all those managers who are evaluating whether to adopt RFId technology in their organisation or not. This contribution has a relevant practicality, as it helps decision makers to address their decisions relying on a sound conceptual baseline, and on objective evaluations.